Neuropsychological recovery during the first 12 months after severe traumatic brain injury: A longitudinal study with monthly assessments. Issue 7 (9th August 2022) - Schultz, Regina; Tate, Robyn L.; Perdices, Michael
ABSTRACT: Neuropsychologists are commonly asked practical questions about cognitive recovery in the first year following moderate-to-severe traumatic brain injury (TBI), however guiding evidence to provide answers is limited. The design of this longitudinal study rectifies methodological problems in the literature by taking serial assessments on a monthly basis from 3- to 12-months post-trauma in a severe TBI sample ( n = 23), and using four alternate forms of a brief yet sensitive cognitive assessment battery. Fifteen variables sampling seven cognitive domains were used: orientation, attention, processing speed, executive function, memory, language and visuospatial function. A matched control group ( n = 23) was used to establish equivalence of the four alternate forms (no statistically significant differences), document practice effects (no statistically significant differences), and provide a comparison standard of cognitive functioning against which to interpret the TBI recovery curves. Twenty-one of 23 consenting TBI participants continued with the serial assessments. Hierarchical growth model analyses typically revealed linear recovery trajectories over the first 12 months. However, by 12-months post-trauma, a significant proportion (up to 36%) had residual mild to severe impairments in various cognitive domains. These results provide detailed information about patterns of cognitive recovery that also have direct clinical application.